King David, innocent blood, and bloodguilt - Shepherd, David (Oxford University Press, Incorporated, 2023)
Of all the characters bequeathed to us by the Hebrew Bible, none is more compelling or complex than David. This study traces the language of 'innocent blood' and 'bloodguilt' through David's story in the books of Samuel and 1 Kings, to understand how this concept shapes the entirety of David's history.